2001
DOI: 10.1063/1.1421618
|View full text |Cite
|
Sign up to set email alerts
|

Nonideal magnetohydrodynamic Kelvin–Helmholtz instability driven by the shear in the ion diamagnetic drift velocity in a high-β plasma

Abstract: A two-dimensional nonideal magnetohydrodynamic eigenmode equation for the most dangerous perturbation (k∥=0) is derived for a high-β plasma by making use of the generalized Ohm’s law and becomes identical to the equation describing the two-dimensional hydrodynamic stability. When the pressure is nonuniform, the density is uniform, and there is no unperturbed electric field or gravity, a Kelvin–Helmholtz instability, which is driven by the shear in the ion diamagnetic drift velocity, is found. When the unpertur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…2(a)], in the latter case (monotonic q) it is stable. In contrast, higher-m modes such as (6, 3) and (12,6) have similar growth rates in both cases, so for these the coupling between the resonances does not seem to play a crucial role.…”
mentioning
confidence: 97%
“…2(a)], in the latter case (monotonic q) it is stable. In contrast, higher-m modes such as (6, 3) and (12,6) have similar growth rates in both cases, so for these the coupling between the resonances does not seem to play a crucial role.…”
mentioning
confidence: 97%
“…They have observed that the rapid development of a short wavelength, lower hybrid drift instability in the current sheet is followed by the slow development of long wavelength current sheet kinking. They calculated the growth rate and the wave number of the kink modes for the realistic mass ratio and found an excellent agreement between those obtained by simulation results and those calculated analytically for the present new K‐H instability driven by the shear in the ion diamagnetic drift velocity [ Miura , 2001]. Therefore even in collisionless plasmas, where the present fluid analysis is not strictly applicable, the existence of the present new K‐H instability is indicated.…”
Section: Discussionmentioning
confidence: 52%
“…Since a temporal growth of the instability is considered, k is real and ω is complex. When the density is nonuniform, the eigenmode equation for the x component of the velocity perturbation δv x becomes [ Miura , 2001] where V 0 (x) is given by in the present simplified model. In general, V 0 (x) is given by the sum of the E × B drift and the ion diamagnetic drift as given by .…”
Section: Dispersion Equations and Dispersion Curvesmentioning
confidence: 99%
See 2 more Smart Citations